Collaborative Learning in the Digital Era: Strategies to Prepare Primary School Students to Face the Challenges of the 21st Century - Latifah, Alia; Kartika, Ika (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2023)
Various aspects of people's lives have experienced changes in line with the development of the era of globalization and openness. 21st century education demands the need for a shift in mindset in teaching and learning methods, with an emphasis on developing 21st century skills as a top priority to equip students with relevant and competitive abilities. Learning at this time must be based on the four skills in 21st century learning. One method that can develop these skills is the collaborative learning method.The research method used is qualitative with data collection techniques in the form of interviews. The subject of this research is a class V teacher in the city of Yogyakarta. The research results revealed that21st century skills is a narrative to change the mindset of educators. Things that need to be paid attention to are not only the academic aspects of students, but also life skills such as collaboration and communication. Collaborative learning is a teacher's effort to create a learning environment that prepares students to face the challenges and opportunities of the 21st century. Through a collaborative approach, students will not only develop academic knowledge, but also the skills and attitudes necessary to succeed in their lives.